HUBUNGAN ANTARA ADVERSITY QUOTIENT DENGAN PRESTASI BELAJAR SISWA SMP NEGERI 4 MUARA BATANG GADIS - haddiris; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
This study aims to determine the relationship between intelligence adversity with learning achievement in class VIII SMP Negeri 4 Muara Batang Gadis. This study uses a quantitative research approach with the correlation method. This research includes population research. The subjects used were all students of class VIII SMP Negeri 4 Muara Batang Gadis, totaling 32 students. The data in this study were obtained using the adversity intelligence scale and student report cards in the first semester. Adversity quotient here refers to aspects of control, origin and ownership, reach, and endurance. And learning achievement in this study is the value or result obtained from the evaluation or other aspects which are quantified and reflected in student report cards in the first semester.